2021
DOI: 10.9734/jpri/2021/v33i28a31518
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Efficacy of Prebiotics and Probiotics as Dietary Supplements in Rats with Gastric Ulcer

Abstract: Gastric ulcer is considered as main problem of gastrointestinal disease, presenting one of the most important health issues in all societies. This comparative study designed to explore the anti-ulcerogenic role of probiotics and prebiotics and to evaluate the most potent effect against gastric ulcer. Sixty rats were distributed into 6 groups : G1 Healthy control; G2 gastric ulcer (GU), ulcer was induced by four oral doses of Aspirin 200 mg/kg b.w./week ;G3 Prebiotics (PreB) administered orally group ( 0.5 g/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…The fermentation product of FOS by beneficial bacteria in the large intestine is SCFAs that indirectly scavenge ROS. [28,32] Further, it could be suggested that FOS supplementation might have increased the beneficial bacterial population that protected the gut epithelium from oxidative stress. As reported earlier, this study's significantly decreasing body and gut weight indicates LPS-induced systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation product of FOS by beneficial bacteria in the large intestine is SCFAs that indirectly scavenge ROS. [28,32] Further, it could be suggested that FOS supplementation might have increased the beneficial bacterial population that protected the gut epithelium from oxidative stress. As reported earlier, this study's significantly decreasing body and gut weight indicates LPS-induced systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, B. cereus, co-infection with avian influenza virus H9N2 or Chlamydia psittaci induced GEU, respiratory distress and pneumonia in SPF chickens (Zhang et al 2019;Zuo et al 2020). Gastric ulcers are initiated and exacerbated by increased acid secretion and a weakened mucosal barrier (Al-garni et al 2021). Feed microbial contamination will generate the majority of biogenic amines (histamine) which catalyzes the secretion of gastric acid.…”
Section: Etiology Of Geu In Poultrymentioning
confidence: 99%